Beginning Reading Instruction for Students at Risk for Reading Disabilities: What, How, and When - Coyne, Michael D.; Zipoli, Richard P.; Ruby, Maureen F. (Intervention in School and Clinic, 2006)
In this article, the authors assist teachers who are working with young students at risk for reading disabilities by helping make sense of the large—but unwieldy—scientific knowledge base. They offer a conceptual framework for thinking about beginning reading instruction and intervention across three dimensions: the content of instruction (what to teach), the delivery of instruction (how to teach), and the timing of instruction (when to teach). The authors discuss each of these dimensions and describe how teachers can use them to help organize and make sense of what we know about beginning reading instruction for students experiencing reading difficulties.
Keywords: dept.cmd; peer-reviewed

Interdisciplinary Management of Stroke Clients. - Purdy, Mary H. (2006)
Keywords: dept.cmd; faculty_collection; sabbatical_report

Focused stimulation for a child with autism spectrum disorder: A treatment study - Grela, Bernard G.; McLaughlin, Kathryn S. (Journal of Autism and Developmental Disorders, 2006)
This study explored the use of focused stimulation as an intervention technique for a three-year-old boy diagnosed with autism spectrum disorder (ASD). His parents were trained to use focused stimulation to facilitate comprehension of what is x doing question forms. Responses to question probes were collected at both pre- and post-treatment intervals. At the beginning of the study, the child did not respond correctly to any of the target questions. Following intervention, the child made significant gains towards the target goal, but little change towards a control goal used for comparison. These findings provide preliminary support for the usefulness of focused stimulation as an intervention strategy for at least some children with ASD.
Keywords: Attention; Autism spectrum disorder; Autistic Disorder; Child, Preschool; Comprehension; Early Intervention (Education); Focused stimulation; Follow-Up Studies; Generalization (Psychology); Humans; Imagination; Imitative Behavior; Language Development Disorders; Language Therapy; Male; Natural language procedures; Parent intervention; Play and Playthings; Speech Perception; article; autism; brain function; case report; child parent relation; cognitive therapy; comprehension; dept.cmd; focused stimulation; human; information processing; language; language development; male; peer-reviewed; preschool child; priority journal; questionnaire; statistical significance

Prediction of strategy usage by adults with aphasia - Purdy, Mary; Koch, Amy (Aphasiology, 2006)
Background: Management of aphasia often focuses on training augmentative communication strategies such as communication books, computerised systems, gestures, writing, or drawing. Although many individuals are able to acquire a targeted skill in a structured format, many do not successfully use the trained skill in more functional situations. Training alternative communication strategies can be a time-consuming project; thus, it would be beneficial if speech-language pathologists could predict, a priori, how a patient may respond to this type of treatment approach. It has been hypothesised that use of augmentative communication strategies requires executive functioning, specifically cognitive flexibility, which may be impaired following brain damage. Therefore, assessment of cognitive flexibility may help clinicians determine which persons with aphasia would most likely benefit from training of augmentative communication strategies. Aims: The purpose of this study was to develop a measure of cognitive flexibility and to determine whether this measure predicted strategy usage during a functional communication task. Methods and Procedures: A novel scoring system for the Communicative Abilities in Daily Living (CADL) was developed to capture the degree of participants' cognitive flexibility. This score was correlated with the Wisconsin Card Sorting Test (WCST), to determine the validity of the scoring system. The CADL cognitive flexibility score was then correlated with performance on a referential communication task. A multiple regression analysis was conducted with severity of aphasia as an additional predictor variable. Outcomes and Results: There was a significant correlation between the cognitive flexibility score from the CADL and the WCST, confirming the validity of the scoring system as a measure of cognitive flexibility. Results of the regression analysis demonstrated a significant relationship between the cognitive flexibility score and strategy usage on a functional communication task. This relationship remained significant when the overall severity of aphasia was added to the regression analysis, suggesting that cognitive flexibility is a stronger predictor of strategy usage than severity of aphasia. These results may provide clinicians insight into which individuals would benefit most from the training of compensatory strategies, leading to the development of more appropriate goals and treatment methods.
Keywords: adult; aged; aphasia; apraxia; article; clinical article; cognition; comorbidity; computer assisted tomography; control strategy; coping behavior; dept.cmd; disease association; disease severity; drawing; facilitated communication; fluency disorder; gesture; human; peer-reviewed; prediction; verbal communication; writing

Standardised speech-language tests and students with intellectual disability: a review of normative data. - Cascella, Paul W (Journal of intellectual & developmental disability, 2006)
Background: Before a school speech-language pathologist (SLP) utilises a standardised speech-language test with a student with intellectual disability (ID), the clinician should carefully consider the purpose of the test and whether the test includes students with ID in the normative group. Method: This project reviewed 49 tests published between 1994 and 2004 and their applicability to students with ID. Results: Students with mild ID were included in the norm group for 23 of the tests, but no tests included students with more significant ID. Separate norms for students with mild ID were included in 15 tests, but none met Salvia & Ysseldyke's (1995) suggested requirement that at least 100 students be included to represent a specific subgroup. A majority of the tests assessed receptive and expressive vocabulary, syntax, and grammar but no recent test measured a student's pragmatic communication. Conclusions: Clinicians are encouraged to supplement standardised tests with non-standardised procedures to document students' pragmatic, social, and functional communication abilities. © 2006 Australasian Society for the Study of Intellectual Disability Inc.
Keywords: *Intellectual Disability; *Language Disorders/di [Diagnosis]; *Language Disorders/ep [Epidemiology]; *Language Tests; *Speech Disorders/di [Diagnosis]; *Speech Disorders/ep [Epidemiology]; Humans; Intellectual disability; Language Disorders; Language Tests; Language test; Mental Retardation; Reference Values; Severity of Illness Index; Speech Disorders; Speech test; Student; adolescent; article; child; dept.cmd; diagnostic value; grammar; human; interpersonal communication; linguistics; major clinical study; mental deficiency; social adaptation; social aspect; social status; speech analysis; speech language pathologist; student; systematic review

An electrophysiologic approach to APD - Jirsa, Robert E; Musiek, Frank E (The Hearing journal, 2006)
Keywords: audiology; auditory cortex; auditory discrimination; auditory processing disorder; auditory stimulation; auditory threshold; dept.cmd; electrophysiology; evaluation; hearing acuity; human; hypoacusis; language; neurophysiology; short survey; speech perception; temporal lobe; voice onset time